Comparative Protection of Cowpea, Vigna unguiculata (L.) Walpers Against Field Insect Pests Using Cashew Nut Shell Liquid and Cypermethrin (Cymbush) - Olotuah, O.F.; Ofuya, T.I. (Pakistan Journal of Nutrition, 2010)
The efficacy of ethanolic extract of Cashew Nut Shell Liquid (CNSL) in protecting Cowpea, Vigna unguiculata L. against field insect pests was ascertained through two field trials at two different planting seasons by comparing with a suitable insecticide, Cymbush 10 EC containing 100 g Cypermethrin per litre of water under natural infestation at Akungba-Akoko, Nigeria. The liquid which is viscous and contains Phenolic compounds was first standardized in the screen house using concentrations of 0.01, 0.1, 0.25, 0.5 and 1.0% to determine a marginal position of high protective capability and non-toxicity to the leaves. About 1.0% proved most effective and it was subsequently transferred to the field for comparison with Cymbush. CNSL was evaluated through the assessment of Insect Pest Number and Percentage Flower Infestation. From these, results were obtained on pod characteristics, yield and yield components, which showed that the 1.0% formulation of CNSL selected was as effective as Cymbush showing a comparatively higher protective ability.